1992
DOI: 10.1002/mcs.1220040603
|View full text |Cite
|
Sign up to set email alerts
|

Verification of nonproduction of chemical warfare agents: II. Large volume injections in microcolumn liquid chromatography using flame photometric detection

Abstract: Abstract. The sensitivity and separation performance of microcolumn liquid chromatography coupled with a flame photometric detector were considerably improved by the direct injection of large sample volumes (approximately 10 pL) and by peak compression. Extremely narrow peaks can be obtained by adding displacers such as hydrochloric acid (ion-exchange mode) or n-butanol (reversed-phase mode) to the sample.The system was used for the determination of ethyl methylphosphonic acid, isopropyl methylphosphonic acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In our earlier work [16][17][18][19] on the coupling of micro-LC with GC detectors, it was found that by combining heating and sufficient cooling, only a small zone (<1 mm) at the end of the liquid introduction capillary is heated. The thermal heat at that zone, which was originally generated by the detector flame, results in a pulsed evaporation and subsequently presumed plug-type liquid introduction as discussed earlier.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our earlier work [16][17][18][19] on the coupling of micro-LC with GC detectors, it was found that by combining heating and sufficient cooling, only a small zone (<1 mm) at the end of the liquid introduction capillary is heated. The thermal heat at that zone, which was originally generated by the detector flame, results in a pulsed evaporation and subsequently presumed plug-type liquid introduction as discussed earlier.…”
Section: Resultsmentioning
confidence: 99%
“…Eluent Jet Interface. The eluent jet interface is the successor of interfaces originally developed for the coupling of micro-LC [16][17][18][19] and CE 23 with GC detectors. The liquid introduction process is based on a sharp temperature gradient at the tip of the fusedsilica liquid introduction capillary (see A in Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers have been published on the analysis of chemical warfare agent degradation products using either gas chromatography/mass spectrometry (GC/MS) or high-performance liquid chromatography (HPLC) with fluorescence detection. The limitations of the methods used in these studies include the following: insufficient sensitivity, interference from naturally occurring components in the matrixes, requirement for derivatization, or long analysis times. Others have reported on microcolumn liquid chromatography and CE with flame photometric detection for the determination of a series of organophosphoric and organophosphonic acids in environmental samples. , Also, ion chromatography (IC) can be used for the analysis of alkylphosphonic acids and their monoesters. The IC separation requires gradient elution, which adds substantially to the analysis time, makes retention times less reproducible, produces more waste solvent, and requires more sophisticated instrumentation. CE has also been used as an alternative approach, as it offers short analysis times, little sample preparation other than dilution and filtration, and flexibility in formulating electrolytes to minimize matrix interference. Also, because the required daily solvent/buffer usage is measured in milliliters as compared to liters with HPLC and IC, the portability of instrumentation dramatically improves, as well as allowing analysis of much smaller samples.…”
mentioning
confidence: 99%
“…Several papers have been published on the analysis of chemical warfare agent degradation products using high-performance liquid chromatography (HPLC) with fluorescence detection, and gas chromatography/mass spectrometry (GC/MS). The limitations of the methods used in these studies include the following: insufficient sensitivity, interference with naturally occurring components in the matrixes, required derivatization, or long analysis times. Microcolumn liquid chromatography and capillary electrophoresis (CE) with flame photometric detection for the determination of a series of organophosphoric and organophosphonic acids in environmental samples have been reported. , Recently, it has been reported that ion chromatography (IC) can be used for the analysis of the IMPA, PMPA, ethyl methylphosphonic acid (EMPA), and MPA. Through the use of cleanup steps (Ag-form cartridges) to reduce chloride and ethylenediaminetetraacetic acid (EDTA) to remove transition metals, and a preconcentration anion-exchange injection setup, IC detection limits in the lower or submicrogram per liter range and detectability in field samples (groundwater/soil leachate) in the single-digit to low double-digit microgram per liter range have been reported . However, this approach involves a rather demanding procedure and appears vulnerable to sample matrix issues when pushed to these limits.…”
mentioning
confidence: 99%